PERTANGGUNGJAWABAN PIDANA ATAS PENYALAHGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PRODUKSI KONTEN HOAKS DAN DEEPFAKE DI MEDIA SOSIAL - Cantika, Naila; Hidayat, Feliciya Archie; Indriana, Patricia Sherly; Sirait, Frengki Riski; Rasyid, Yennie Agustin Mahroennisa (STKIP Pesisir Selatan, 2025)
The advancement of artificial intelligence (AI) technology offers significant opportunities in digital content production, but its improper use for hoaxes and deepfakes on social media platforms leads to adverse effects, such as damaging reputations, spreading false news, and jeopardizing information security. This paper examines criminal liability for AI misuse by considering legal aspects, difficulties in verification, and the effectiveness of regulations in Indonesia, while emphasizing the need for adaptive rules to prevent manipulated content.The main discussion includes the concept of AI as a system capable of independent learning, hoaxes as inaccurate data disseminated, and deepfakes as techniques for altering media to resemble the original. The deepfake case involving President Prabowo illustrates the real dangers. The classification of criminal acts encompasses practices of fraud and defamation. The application of relevant articles in the Indonesian Criminal Code is evaluated, although challenges in proof include technical and legal obstacles. Criminal accountability involves penalties for individuals and corporations. Gaps in legislation urge regulatory changes to align with AI advancements.